Essays on tax, accountability and fiscal capacity in sub-Saharan Africa - Dom, Roel (2019)
This thesis consists of three self-contained essays exploring the interaction between fiscal capacity and state-building, as well as the impact of external relations on fiscal capacity in sub-Saharan Africa.